Sources of Organizational Stress Among Faculty Members in the West Bank Universities - Abed M. Assaf (My University, 1996)
The goals of this study were first to determine the main sources of faculty members stress in the Palestinian territories which have been occupied by Israel since 1967. Second to identify the contribution of the demographic variables of age, sex, marital status, degree, college, years of teaching experience, and professional rank on faculty members perception of organizational stressors as independent variables, which accounted for faculty members stress as a dependent variable. The sample consisted of 136 faculty members selected randomly from four universities in the West Bank. To collect the data, a scale of the sources of stress was constructed, validated and administered to the sample. The results of the study showed that the contribution of all the independent variables was (18.6%). The largest contribution was due to sex (6%) followed by years of teach experience (5%), then social status (3.1%), age (3%), professional rank (6.0%) colleges (5.0%), and finally the academic degree 4.0%. The study showed also that there are significant mean differences due to both sex and teaching experience on organizational stressors. The other demographic variables were not statistically significant at .05. Therefore, the results suggest that organizational stressors are the most important factors in determining stress among faculty members. The top four were found to be: 1- Frequent shutdown of the universities and the continuous threat of closure by the Israeli military authorities. 2- Not having the right person in the right person in the right place of position. 3- Lack of feeling of self-security and for their own family, and of the students. 4- Lack of qualifications in the administrators in running the universities.

تهدف هذه الدراسة أولا: إلى تحديد مصادر الضغط النفسي عند مدرسي الجامعات في الضفة الغربية المحتلة من قبل إسرائيل سنة 1967، وثانيا: إلى تحديد مدى مساهمة كل من المتغيرات الديموغرافية التالية: العمر، والجنس، والحالة الاجتماعية ، والدرجة العلمية والكلية، وعدد سنوات الخبرة، والرتبة العلمية في الضغوطات النفسية التي يتعرض لها الأكاديميين. تكونت عينة الدراسة من "136" عضو هيئة تدريس اختيروا بالطريقة العشوائية، وتم بناء مقياس لقياس الضغط النفسي عند الأكاديميين وطبق على أفراد العينة بعد أن استخرجت دلالات صدقه وثباته ثم أجرى التحليل الإحصائي المناسب. أشارت نتائج الدراسة إلى أن مساهمة المتغيرات الديموغرافية كانت بنسبه (6ر18%). كان أهم المتغيرات هو متغير الجنس حيث فسر ما نسبة 6%، ثم عدد سنوات الخبرة 5%، ثم الحالة الاجتماعية 3.1% ، ثم العمر 3%، ثم الرتبة العلمية 0.6%، ثم الكلية 0.5%وأخيرا الشهادة العلمية 0.4%. كما بينت نتائج هذه الدراسة إلى وجود فروق ذات دلال إحصائية بين متغيري الجنس وعدد سنوات الخبرة ومتغير الضغط النفسي بينما المتغيرات الديمغرافية الأخرى لم يكن لها أي دلاله إحصائية. هذه النتيجة قد تعني أن ضغوطات العمل هي من العوامل الرئيسية في الضغط النفسي أو الإجهاد عند الأكاديميين في جامعات الضفة الغربية والتي تحد من إنجازهم العلمي والأكاديمي وأهمها: 1. إغلاق الجامعات بشكل متكرر ومستمر أو التهديد بإغلاقها. 2. عدم وضع الرجل المناسب في المكان المناسب. 3. عدم توفر الأمن لي ولأفراد أسرتي وللطلبة. 4. عدم توفير الكفاءة الإدارية في إدارة المؤسسة التي أعمل بها.
مصادر الإجهاد أو الضغط النفسي لدى مدرسي الجامعات في الوطن المحتل/ الضفة الغربية